THE EFFECT OF ZINC TREATED SOIL ON THE GROWTH AND DEVELOPMENT OF VERNONIA AMYGDALINA DEL. PLANT (FUDMA JOURNAL OF SCIENCES, 2023)
The effect of zinc on the growth and development of Vernonia amygdalina was investigated in this study. Identical stem cuttings of the plants were collected and sown in buckets filled with 5kg dry soil. The experiment was made up of control and four different concentrations (25, 50, 75 and 100mg/kg) in three replicates. Data were collected monthly for 12 months. Result on plant height, number of leaves, number of branches and girth of stem showed an adverse effect of treatment except for leaf area which was enhanced. For example, when control value at 12 MAT was 35.67 ± 7.54, for number of leaves, the 25 mg / kg, 50 mg / kg, 75 mg / kg and 100 mg / kg recorded 11.33 ± 0.88, 11.67 ± 1.20, 12.33 ± 2.19 and 12.33 ± 2.03 respectively. There was decreased soil pH, nutrients and microbial load. There was however an increase in soil carbon. These effects were along the concentration gradient. Zinc uptake by plant was within tolerable limits
Keywords: treatment, gradient, zinc, Vernonia amygdalina